Data-centric security : towards a utopian model for protecting corporate data on mobile devices - Mayisela, Simphiwe Hector (Rhodes University, Faculty of Science, Department of Computer Science, 2014)
Data-centric security is significant in understanding, assessing and mitigating the various risks and impacts of sharing information outside corporate boundaries. Information generally leaves corporate boundaries through mobile devices. Mobile devices continue to evolve as multi-functional tools for everyday life, surpassing their initial intended use. This added capability and increasingly extensive use of mobile devices does not come without a degree of risk - hence the need to guard and protect information as it exists beyond the corporate boundaries and throughout its lifecycle. Literature on existing models crafted to protect data, rather than infrastructure in which the data resides, is reviewed. Technologies that organisations have implemented to adopt the data-centric model are studied. A utopian model that takes into account the shortcomings of existing technologies and deficiencies of common theories is proposed. Two sets of qualitative studies are reported; the first is a preliminary online survey to assess the ubiquity of mobile devices and extent of technology adoption towards implementation of data-centric model; and the second comprises of a focus survey and expert interviews pertaining on technologies that organisations have implemented to adopt the data-centric model. The latter study revealed insufficient data at the time of writing for the results to be statistically significant; however; indicative trends supported the assertions documented in the literature review. The question that this research answers is whether or not current technology implementations designed to mitigate risks from mobile devices, actually address business requirements. This research question, answered through these two sets qualitative studies, discovered inconsistencies between the technology implementations and business requirements. The thesis concludes by proposing a realistic model, based on the outcome of the qualitative study, which bridges the gap between the technology implementations and business requirements. Future work which could perhaps be conducted in light of the findings and the comments from this research is also considered.
Keywords: Computer security; Computer networks -- Security measures; Business enterprises -- Computer networks -- Security measures; Mobile computing -- Security measures; Mobile communication systems -- Security measures